INVESTIGATING THE PROGRESSION AND MANAGEMENT OF DIABETIC RETINOPATHY: A CLINICAL PERSPECTIVE - Yusupov Mirza Murodovich (World Scientific Research Journal, 2025)
Annotation: Diabetic retinopathy (DR) is a common microvascular complication of diabetes mellitus and a leading cause of blindness in working-age adults worldwide. It results from prolonged hyperglycemia, which damages retinal blood vessels, leading to visual impairment. This article explores the progression of diabetic retinopathy, current diagnostic tools, and management strategies. Using clinical observations and recent research data, the methodology involves examining patients at various stages of the disease and assessing the efficacy of interventions such as glycemic control, laser photocoagulation, and intravitreal injections. The results show a strong correlation between early intervention and disease stabilization. This study highlights the need for routine screening and integrated treatment approaches to prevent vision loss due to DR.